Pulsed electric field (PEF)–processed 6-shogaol-rich ginger extract protects β-Thalassemic red blood cells from iron-induced oxidative stress and hemolysis - Hataichanok Chuljerm; Narisara Paradee; Kornvipa Settakorn; Somdet Srichairatanakool; Artit Yawootti; Kanokwan Kulprachakarn; Wason Parklak; Pimpisid Koonyosying (PLoS ONE, 2025)
β- thalassemia is the genetic blood disorder characterized by ineffective beta-globin chain synthesis. The increased iron absorption and frequently blood transfusion result in iron overload and the production of reactive oxygen species (ROS). ROS causes lipid peroxidation and membrane damage in red blood cells (RBCs), culminating in hemolysis and anemia. This study investigated the protective effects of ginger extract against iron induced oxidative damage in thalassemic RBCs. The pulsed electric field (PEF) technique with high-voltage electric pulses, was used for ginger extraction. The PEF significantly enhanced the yield of bioactive compounds, 6-shogaol and total phenolic content compared to conventional maceration technique. The 6-shogaol-rich ginger extract possessed a potent antioxidant activity by scavenging free radicals (ABTS•+ and DPPH•), and inhibiting of AAPH-induced RBC hemolysis in both healthy and β-thalassemic RBCs. Additionally, the extract exhibited iron-chelating properties by decreasing non-heme iron levels on the RBC membrane, thereby reducing lipid peroxidation reaction. These findings suggest that 6-shogaol-rich ginger extract processed with PEF could serve as a potential therapeutic agent, exhibiting powerful antioxidant and red blood cell membrane iron-chelating properties to protect against oxidative damage and hemolysis in iron-overloaded β-thalassemia patients.